Surface liming triggers improvements in subsoil fertility and root distribution to boost maize crop physiology, yield and revenue - Bossolani, João William [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP]; Momesso, Letusa [UNESP]; Portugal, José Roberto [UNESP]; Moretti, Luiz Gustavo [UNESP]; Garcia, Ariani [UNESP]; de Cássia da Fonseca, Mariley [UNESP]; Rodrigues, Vitor Alves [UNESP]; Calonego, Juliano Carlos [UNESP]; dos Reis, André Rodrigues [UNESP] (Springer Nature, 2022)
Background and aims: Liming is widely used to alleviate soil acidity worldwide. However, the vast majority of studies with liming are restricted to agricultural systems that incorporate lime into the soil, not considering its effects as surface applications. Although liming effects on soil fertility and crop yield are well understood, there are few studies that elucidate the role of soil improvements in the established crop physiology and the revenue in lime-amended soils, especially when cultivated in regions prone to agroclimatic risks. Here, we address the effects of surface liming, for three growing seasons (2017–2019) subsequent to the lime treatment (2016), on soil fertility, root growth, crop nutrition, photosynthetic pigment concentrations, gas exchange parameters and production costs of maize cultivated in a tropical region on an acidic soil with low water regime. Methods: The treatments consisted of four dolomitic lime doses applied to the soil surface as follows: i) control (untreated soil), ii) half the recommended dose (½ RD), iii) full recommended dose (1 RD) and iv) twice the recommended dose (2 RD). Results: Surface liming increased soil fertility, and higher doses provided better results. Ca2+ and Mg2+ concentrations increased at greater depths under higher lime doses, directly influencing maize root growth. Even under low water availability, also in the driest year of 2018, this liming induced improvement of growing conditions and increased growth was observed’. Maize grown under lime at 2 RD exhibited better nutrition, improved chlorophylls concentration, photosynthetic parameters and water use efficiency. As a result, both shoot growth and grain yield also increased. Net profit in the first growing season was higher in 1 RD, whereas in the two following growing seasons the application of 2 RD resulted in higher revenue. Conclusions: Increased water use efficiency, chlorophyll and photosynthesis were the main physiological traits regulating the growth and yield of maize plants in response to lime supply. Additionally, root development was favoured in the entire soil profile, mainly in deeper layers, after improvements on soil fertility by cascading effects of liming. These results were more prominent in 2RD lime-amended soil, which also resulted in greater net profit over the 3 years studied.
Keywords: Acidic soils; Field experiment; Photosynthesis; Root growth; Water use efficiency